Biliary adenofibroma: a precursor lesion of intrahepatic cholangiocarcinoma - Parkhi, Mayur; Joshi, Rashmi; Kumar, Manish; Sharma, Aditi; Mitra, Suvradeep; Kaman, Lileswar (Autopsy and Case Reports, 2023)
Biliary adenofibroma (BAF) is an uncommon liver tumor with a high propensity for malignant transformation. The histomorphology of BAF with malignant transformation can show a spectrum of changes ranging from benign, dysplastic to frank malignancy. Thus, the diagnosis of BAF imposes the pursuit of dysplasia/ malignancy focus. We presented a case of intrahepatic cholangiocarcinoma arising from BAF in a 49-year-old woman with detailed histomorphology. We also performed a PubMed database search and tabulated all previously reported cases of BAF with dysplasia/ malignant transformation. A statistic comparison of age, sex ratio, size of the tumor, and survival following complete resection between BAFs with and without dysplasia/ malignancy from the retrieved data is presented. Our analysis did not highlight any statistically significant difference between BAFs with and without dysplasia/ malignancy in age, sex ratio, tumor size, and survival following complete surgical resection. Our study highlights the histopathology and immunohistochemistry of a case of BAF with malignant transformation and highlights the importance of this diagnosis in management. Further longitudinal studies on a larger cohort of patients are required to validate our findings.